Neuronal chloride transport tuning: poster abstract - Sammler, Esther; Titz, Stefan; Hormuzdi, Sheriar (The lancet, 2015)
Abstract Background Epilepsy is characterised by disturbed neuronal activity in the brain rendering it more susceptible to seizures. An understanding of the molecular mechanisms by which the balance between excitability and inhibition in neuronal networks is controlled will help to devise better treatment options. Hyperpolarising synaptic inhibition through GABA (γ aminobutyric acid type A) and glycine receptors depends on the presence of the neuronal cation-chloride-cotransporter protein, KCC2. Several transcriptional and post-transcriptional mechanisms have been shown to regulate KCC2 and thereby affect the polarity and efficacy of inhibitory synaptic transmission. However, it is unknown whether regulation of KCC2 enables the transporter to attain different levels of activity, thus allowing a neuron to modulate the strength of inhibitory synaptic transmission to its changing requirements. We therefore investigated whether phosphorylation can allow KCC2 to achieve distinct levels of intracellular chloride ion concentrations in neurons. Methods A variety of KCC2 alanine dephosphorylation mimics were created and NH4+-induced pHi shifts were used in cultured hippocampal neurons to quantify the rate of KCC2 transport activity exhibited by these mutants. The association between KCC2 transport strength and GABAA receptor-mediated current amplitudes was investigated by performing gramicidine perforated-patch recordings. The correlation between reversal potential of GABAergic currents (EGABA) and NH4+-induced pHi shifts enabled an estimate of the range of chloride extrusion possible by kinase-phosphatase regulation of KCC2. Finally, we used the Goldman-Hodgkin-Katz equation to examine how EGABA would vary with increasing concentrations of extracellular K+ in neurons expressing KCC2 mutants with different rates of transport. Findings KCC2 transport strength varied considerably in magnitude (from −0·02 to −1·00 pHi shifts) depending on the combination of alanine mutations present on the protein. KCC2 transport strength determined the direction and magnitude of GABAA receptor-mediated current amplitudes and was observed to have a linear correlation with the reversal potential of GABAergic currents. Interpretation Our findings highlight the considerable potential for regulating the inhibitory tone by KCC2-mediated chloride extrusion. Transport can be enhanced to sufficiently high levels that hyperpolarising GABAA responses can be obtained even at high extracellular K+concentrations and in neurons with an extremely negative resting membrane potential. We conclude that cellular signalling pathways might act together to alter the state of KCC2 phosphorylation and dephosphorylation and thereby tune the strength of synaptic inhibition.Funding Royal Society.